Plasmonics: How Effective is Plasmonic Enhancement of Colloidal Quantum Dots for Color‐Conversion Light‐Emitting Devices? (Small 48/2017). Issue 48 (19th December 2017) - Park, Hyun Chul; Isnaeni,; Gong, Suhyun; Cho, Yong‐Hoon
Abstract : In article1701805, Y.‐H. Cho and co‐workers report that a blue LED (light‐emitting diode) simultaneously excites the layer of red quantum dot–silver nanodisk hybrid structures, and the layer of green quantum dot–aluminum nanodisk hybrid structures in in‐depth systematic finite‐difference time domain simulations of excitation, spontaneous emission, and quantum efficiency enhancement. Excitation enhancement and spontaneous emission enhancement results in increased quantum dot emission intensity, which may be applied in quantum dot based LEDs.